Anti-SRP myositis: a diagnostic and therapeutic challenge - Merve Cansu Polat; Didem Ardıçlı; Banu Çelikel Acar; Beril Talim; Nesrin Şenbil; Elif Çelikel (The Turkish Journal of Pediatrics)
Background. Anti-signal recognition protein (anti-SRP) myopathy is a rare idiopathic inflammatory myopathy in children. Herein, a 3-year-old patient with severe anti-SRP myopathy showing a rapidly progressive disease course is presented in order to increase the awareness of pediatricians about idiopathic inflammatory myopathies.